2020
DOI: 10.33259/jlivestsci.2020.1-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of turmeric rhizome powder on growth, carcass and meat quality of Japanese quails fed sorghum-soybean-based diets

Abstract: This study was conducted with 600, seven day-old mixed Japanese quail chicks to investigate the effects of varying levels of turmeric rhizome powder (TRP) on growth parameters, carcass traits and organoleptic properties of the breast muscles. The chicks were randomly assigned to five dietary groups containing 0.00, 0.25, 0.50, 0.75 and 1.00% TRP of sorghum-soybean based diet in a completely randomized design. Each treatment had six replicates of 20 birds each and was studied from 7-42 days of age. Growth perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
3
5
0
Order By: Relevance
“…In the course of the experiment, it was found that versus control, due to the highest growth rate, the meat chickens in the second experimental group consumed mixed feed 9.00% less per unit of received gross formation. It shows that the best dose of Epofen feeding by reducing the risk of T-2 toxicosis in broiler-chickens is 200 g/t feed, which improves the basic economic and useful qualities (Dzhaboeva et al, 2019;Kennedy et al, 2019) To ensure high growth rate for broiler chickens, especially at the risk of mycotoxicosis, the problem of increasing the activity of digestive enzymes is of paramount importance, so we studied the effect of different antioxidant doses on the enzymes activity in the content of the muscular stomach (Table 4) and duodenum ( Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…In the course of the experiment, it was found that versus control, due to the highest growth rate, the meat chickens in the second experimental group consumed mixed feed 9.00% less per unit of received gross formation. It shows that the best dose of Epofen feeding by reducing the risk of T-2 toxicosis in broiler-chickens is 200 g/t feed, which improves the basic economic and useful qualities (Dzhaboeva et al, 2019;Kennedy et al, 2019) To ensure high growth rate for broiler chickens, especially at the risk of mycotoxicosis, the problem of increasing the activity of digestive enzymes is of paramount importance, so we studied the effect of different antioxidant doses on the enzymes activity in the content of the muscular stomach (Table 4) and duodenum ( Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…(32) reported that the best antioxidant activity of turmeric is at 0.5% level which causes a significant increase in body weight by stimulating protein synthesis of birds enzymatic system. Another researcher (22) reported that turmeric contains bioactive ingredients like curcumin and curcumoinoids that could stimulate the feed bioavailability and utilization by the quails.…”
Section: Resultsmentioning
confidence: 99%
“…In commercial turmeric, curcumin I represents 70%, curcumin II, 17%, and curcumin III, 3% (LEE et al, 2013). Turmeric contains antioxidant (SUN et al, 2019), anti-inflammatory (HEWLINGS & KALMAN, 2017), antiviral (ALAGAWANY et al, 2015), antitumor, and antimicrobial (MOSELHY et al, 2018) substances that improve body function (SARASWATI et al, 2013a), and consequently, productive performance, as shown by Attia et al (2017), Nuraini & Djulardi (2019, Kennedy et al (2020), andLiu et al (2020). Most of the studies have focused only on the quality of fresh eggs; thus, this study was carried out to evaluate the effect of dietary supplementation with turmeric powder on the productivity and egg quality of Japanese quails as well as on the quality of eggs stored at ambient temperature or under refrigeration for 7 or 14 d.…”
Section: Introductionmentioning
confidence: 95%